--If you lived when there was slavery in America - Kamma, Anne (Scholastic, 2004)
Gives children an overview of daily life as a slave in the U.S., discussing such topics as where slaves slept, what they ate, what "jumping the broom" was, why slaves were not allowed to read or write, and what happened if one tried to run away.